Full and Emptied: Interpreting Christ’s Divinity for Theologies of Religion - Haas, Kristi (Lumen et Vita, 2014)
The concept that “fullness” is to be found in Jesus Christ has been invoked to support the uniqueness of Jesus, including in the context of world religions. Yet the metaphorical sense of fullness is amenable to a variety of interpretations. Is this uniqueness the logical consequence of Christian faith, or an over-reliance on what amounts to a spatial metaphor? Are the uniqueness and primacy of Jesus meant only as praise, or does this also constitute a proposition about Jesus, vulnerable to the logic of non-contradiction? Is a lack or any partial lack of “fullness” to be found in any setting, if all things are created through, by, and for Jesus? This paper explores the concept of the “fullness of truth” in its biblical context, as a doctrinal claim, and in contemporary interpretations in order to offer an analysis of “fullness” in Christ in light of the identity and call of the Church, the sacrament of God's salvific life. Treating fullness as an abstracted premise or proposition leads quickly to an ontotheological interpretation of Jesus' divinity. Instead, we would do well to learn the meaning of the metaphor by attending to its expressions in the life of the Church, a central one of which is the self-emptying love, the communion with which, we are promised, leads into all truth.